2009
DOI: 10.1038/nrendo.2009.81
|View full text |Cite
|
Sign up to set email alerts
|

Pseudohypoparathyroidism type 1a and insulin resistance in a child

Abstract: Background. A 5-year-old white girl with a history of hypothyroidism in infancy presented to the endocrinology clinic of a tertiary hospital. Her physical examination noted a stocky physique, broad chest, short neck and short digits. Two years later, skin examination revealed subcutaneous nodules and acanthosis nigricans.Investigations. Measurement of levels of serum phosphate, parathyroid hormone, ionized calcium and insulin; measurement of peak growth hormone by the arginine-levodopa stimulation test; calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…Patients with PHP1A and PHP1B can develop early-onset obesity, usually in the first 2 years of life 28,44,49,[108][109][110][111] . Noticeably, obesity in adulthood is less severe and less common than in childhood 28 .…”
Section: Additional Frequent Clinical Featuresmentioning
confidence: 99%
“…Patients with PHP1A and PHP1B can develop early-onset obesity, usually in the first 2 years of life 28,44,49,[108][109][110][111] . Noticeably, obesity in adulthood is less severe and less common than in childhood 28 .…”
Section: Additional Frequent Clinical Featuresmentioning
confidence: 99%
“…A Q35X mutation in exon 1 has been associated with growth-hormone deficiency (Germain-Lee, 2003), whereas a de novo, missense mutation, W281R in exon 11, has been linked to progressive osseous heteroplasia, a rare, autosomal-dominant condition that presents in childhood as dermal ossification that progresses to involve deep skeletal muscles (Chan, 2004). Germain-Lee et al(Germain-Lee, 2003) identified a patient with a Q29X mutation, and Nwosu et al (Nwosu, 2009) reported the association of Q29X mutation with a phenotype that includes Albright hereditary osteodystrophy, morbid obesity, acanthosis nigricans, insulin resistance, growth-hormone deficiency, hypothyroidism, and subcutaneous calcification.…”
Section: Genetics Of Albright Hereditary Osteodystrophymentioning
confidence: 99%
“…In those patients in whom defective growth-hormone secretion is suspected, the epiphyseal defects, commonly mischaracterized as bone-age advancement, should not disqualify these children from being considered for growth-hormone therapy. In addition to its effect on statural growth, growth-hormone therapy also seems to improve body composition in patients with PHP 1a (Nwosu, 2009). …”
Section: Growth-hormone Deficiencymentioning
confidence: 99%
See 2 more Smart Citations